First-principles calculation of iron and silicon isotope fractionation between Fe-bearing minerals at magmatic temperatures: The importance of second atomic neighbors. (1st July 2021) - Rabin, S.; Blanchard, M.; Pinilla, C.; Poitrasson, F.; Gregoire, M.
Highlights: This DFT-based study provides new and self-consistent Fe and Si isotope fractionation factors for the main magmatic minerals present in the crust. Iron isotope fractionation factors between Fe 2+ -bearing minerals are not negligible even at magmatic temperatures. For a given temperature and oxidation state, the local cationic environment of Fe or Si is the main factor influencing the isotopic properties of silicate minerals. Fractional crystallization is a viable way to explain the heavy iron isotope signature of the most evolved lavas. Abstract: In order to elucidate the processes involved in iron and silicon isotopes partitioning during magmatic differentiation, it is essential to know the precise value of equilibrium fractionation factors between the main minerals present in the evolving silicic melts. In this study, we performed first-principles calculations based on the density functional theory to determine the equilibrium iron and silicon isotopes fractionation factors between eleven relevant silicate or oxide minerals in the context of magmatic differentiation, namely: aegirine, hedenbergite, augite, diopside, enstatite, fayalite, hortonolite, Fe-rich and Fe-free forsterites, magnetite and ulvospinel. Results show that Fe 2+ -bearing silicate minerals display significant differences in iron isotope fractionation factors that cannot be neglected, even at high temperature (1000 °C). Various physical and chemical parameters control the iron isotopic fractionation of silicate minerals. However, the main parameter, after temperature and the iron oxidation state, is the nature and number of iron second neighbors (i.e. the local chemical composition around Fe atoms). This conclusion is also valid for silicon isotopes. In the investigated nesosilicates and inosilicates, silicon isotope reduced partition function ratios (also called β -factors) show no correlation with the average Si-O bond length, which remains almost constant, but Si β -factors are correlated with the local chemical composition of the minerals. Fractional crystallization is one of the mechanisms, which could explain the evolution of iron isotopic compositions during magmatic differentiation. Using the present theoretical set of equilibrium fractionation factors allows us to assess the impact of inter-mineral isotopic fractionations, and shows that pyroxene appears to be the main mineral phase driving the isotopic evolution to a heavier signature in the most evolved lavas.